2013
DOI: 10.1128/jcm.01019-13
|View full text |Cite
|
Sign up to set email alerts
|

SNaPBcen : a Novel and Practical Tool for Genotyping Burkholderia cenocepacia

Abstract: c Burkholderia cenocepacia is the most prevalent and feared member of the Burkholderia cepacia complex in lung infections of cystic fibrosis (CF). Genotyping and monitoring of long-term colonization are critical at clinical units; however, the differentiation of specific lineages performed by multilocus sequence typing (MLST) is still limited to a small number of isolates due to the high cost and time-consuming procedure. The aim of this study was to optimize a protocol (the SNaPBcen assay) for extensive bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…By using recA gene sequence analysis and multilocus sequence typing, B. cenocepacia may be subdivided into four phylogenetic clusters, IIIA to IIID [7]. However, almost all clinically relevant isolates belong to the IIIA and IIIB groups [8, 9]. Epidemiological studies showed that strains ET-12 and several other epidemic dominant in Canada and Europe are part of the IIIA subgroup [10].…”
Section: Introductionmentioning
confidence: 99%
“…By using recA gene sequence analysis and multilocus sequence typing, B. cenocepacia may be subdivided into four phylogenetic clusters, IIIA to IIID [7]. However, almost all clinically relevant isolates belong to the IIIA and IIIB groups [8, 9]. Epidemiological studies showed that strains ET-12 and several other epidemic dominant in Canada and Europe are part of the IIIA subgroup [10].…”
Section: Introductionmentioning
confidence: 99%
“…The flexibility of the method allows the modification and addition of extra markers in case they prove to be relevant for the genotyping of specific populations (30). In this work, 7 extra markers (At66F, At248F, At359F, At443F, Gl313F, Gy218F, and Ph318F) were defined for B. cepacia and B. contaminans genotyping, in addition to 11 other markers previously defined for B. cenocepacia (13), suggesting that a set of well-characterized markers can be used to genotype Bcc species. The proposed methodology, the SNaPBceBcon assay, was reproducible, practical, and capable of distinguishing the species B. cepacia and B. contaminans and efficiently detected the MLST profiles in our collection of isolates.…”
Section: Intermediate Profilementioning
confidence: 99%
“…Before the primer annealing, touchdown PCR with three successive cycles (total of nine cycles) at increasing temperatures was performed. The strategy used for development of the SNaPBceBcon assay was similar to that previously described for B. cenocepacia (13); the primers are presented in Table 2. The SNaPBceBcon assay was carried out in a final volume of 5 l, as previously described (29).…”
mentioning
confidence: 99%
See 2 more Smart Citations